2011
DOI: 10.1007/s00787-011-0160-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of seclusion and restraint use in children and adolescents: a systematic review

Abstract: Seclusion and restraint are frequent procedures to intervene in aggressive and potentially dangerous patients in psychiatric settings. However, little is known about their utilization and effectiveness in paediatric populations. We aimed to examine the prevalence and determinants of seclusion and restraint utilisation in children and adolescents in psychiatric settings. Using PubMed, PsychInfo and Cinahl, we performed a systematic literature review of studies published in the last 10 years reporting on the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
75
3
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(79 citation statements)
references
References 36 publications
0
75
3
1
Order By: Relevance
“…Adult studies report substantial variability in the use of restraint between nations and hospitals [710]. Studies of restraint use in child and adolescent mental health services report relatively high rates, often at similar or higher levels compared to adult mental health services, and, again, the extent of the use varies considerably [11, 12]. One Finnish national study reported that about 40% of the adolescent inpatients had been restrained in some way during their admission [13].…”
Section: Introductionmentioning
confidence: 99%
“…Adult studies report substantial variability in the use of restraint between nations and hospitals [710]. Studies of restraint use in child and adolescent mental health services report relatively high rates, often at similar or higher levels compared to adult mental health services, and, again, the extent of the use varies considerably [11, 12]. One Finnish national study reported that about 40% of the adolescent inpatients had been restrained in some way during their admission [13].…”
Section: Introductionmentioning
confidence: 99%
“…It is used by disability and mental health services in Australia and many other developed countries mostly to control behaviours that are perceived to be harmful to others (Fryer, Beech, & Byrne, 2004). This practice continues despite a lack of evidence supporting its effectiveness (De Hert, Dirix, Demunter, & Correll, 2011). Evidence demonstrates that it contributes to sometimes significant negative physical and psychological effects (Palazzolo, 2004), and that its use on people with a disability is counter to current service values and places staff and people with a disability in a potentially unsafe situation (Sturmey, 2009).…”
Section: Introductionmentioning
confidence: 97%
“…The rates of restraints and seclusion are considered to be higher in children's mental health settings than in adult settings, despite the extent of the risks associated with using these practices, including trauma, physical injuries, and death (Hert et al . ; Lebel et al . ; Nunno et al .…”
Section: Introductionmentioning
confidence: 99%